HISTORY AND AREAS OF MELON CULTIVATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Written historical records mention that melon cultivation dates back to more than 2000 years ago. Melon seeds dating to the 3-rd century AD were found out at the excavation of Toprakkale castle, 80 km from Berunii. Ak-Saolibii and Moroccan traveller Ibn Batutta (14th century) described in their books the Khorezm melons. Sakheriddin Mukhamed Babur (15th century) and many travellers in subsequent years, travelling in the Maverannakhre area, were fascinated by the excellent taste of melons that were found here. Melon cultivation has been practiced in Central Asia for centuries, and melons are loved and appreciated by people in the region as one of their most valuable food sources.